The Utilization of Social Media Marketing in Destination Management Organizations - Birgit Bosio; Stefanie Haselwanter; Michael Ceipek (6th International OFEL Conference on Governance, Management and Entrepreneurship. New Business Models and Institutional Entrepreneurs: Leading Disruptive Change. April 13th - 14th, 2018, Dubrovnik, Croatia, 2018)
The emerging use of social media fundamentally changes the communication and interaction of humans. Social media applications enable customers to present their thoughts, opinion and ideas through user generated content in social networks and make them visible for a big crowd. Therefore, social media is more than a technological development; it is as social innovation, which highly effects entrepreneurial actions. Especially in the organizational context, the use of social media revolutionizes the way enterprises market their products/services and communicate with their customers. Social media acts as an agent of change within the marketing and communication of organizations. In particular the tourism sector is affected by these disruptive changes. Social media influences and changes the tourism customer journey fundamentally and therefore the interaction between supply and demand sides. The tourism product itself is an intangible and immaterial bundle of services; due to these inherent characteristics potential customers seek reliable information about their potential purchase as well as about possible activities in the destination during their consumption. The diffusion of user generated content on blogs, social networks and video portals provides potential and actual customers with reliable information from other customers; it enables them to share independent opinions and spread the satisfaction or dissatisfaction with their purchase. Social media applications therefore act as a multiplication for the word-of-mouth of customers and potential customers highly rely on independent and unbiased opinions and information of those influencers on social media. These upcoming opportunities and challenges are especially relevant for destination management organizations, which try to coordinate and market the intangible and immaterial tourism product of a destination as a whole. The technological and social innovation of social media applications transformed the classical marketing and communication of these destination management organizations. Destination management organizations are obliged to be present on various channels and to communicate with potential and actual customers throughout the whole customer journey. However, it also enables them to interact directly and communicate in reciprocal way with customers. Nevertheless destination management organizations are still in an experimental stage of utilizing social media applications as a marketing tool. Destination management organizations slowly start to realize the potential benefits of social media as an agent of change. There is still a gap in tourism management literature how these organizations implement social media to market the destination and their tourism product and with what challenges destination management organizations are confronted regarding marketing and communication through social media. Therefore this paper addresses these questions by identifying the utilization of social media in destination management organizations in the Austrian region of Tyrol. In a first step, a quantitative survey was applied to show the use of social media in 34 destination management organizations in the Tyrol. Based on these findings, qualitative interviews with social media managers in the various destinations where conducted to identify the potential opportunities and challenges of social media in tourism. Further, the paper derives recommendations for action for destination management organizations on how they can successfully implement social media into their destination marketing and overcome challenges.
Keywords: 650; Social media; Change management; Disruptive change; Destination management organizations